University Students’ Assessment of a Service-Learning Project for Developing Teaching Materials. - Onieva-López, Juan Lucas; Cremades-García, Raúl; Ramírez-Leyton, John; Ortega-Velasco, María Soledad (The Editorial Board, 2021)
The objective of this study is to determine the opinions of university students undergoing primary school teacher training to develop language teaching material for patients from the Children’s Hospital of Málaga, Spain, using the Service Learning (SL) methodology. Students evaluated this methodology by answering a 16-question questionnaire validated by external researchers. Academic performance was analysed using the Student’s t-test by comparing grades between an intervention and a control group. The results indicated improvements in several areas, including: the level of engagement, transversal competencies, academic performance, level of student satisfaction, and acquisition of teaching material related to the subject.
https://www.ijicc.net/index.php/publication-terms-and-conditions
Keywords: Aprendizaje servicio; Rendimiento académico; Enseñanza superior; Profesores de enseñanza primaria - Formación profesional; Service Learning